Development of Digital Models of Interconnected Electrical Profiles for Rolling–Drawing Wire Mills - Alexandr S. Karandaev; Vadim R. Gasiyarov; Andrey A. Radionov; Boris M. Loginov (Machines, 2021)
The latest development trend in rolling industry is the combination of various technological operations in continuous production lines. In the production of long products, the combination of rolling and drawing processes looks promising. A wire drawing mill developed by the team of authors of this work belongs to the conceptually new, integrated lines. The creation of new integrated rolling mills requires a research phase, where relevant concepts are scrutinized using the methods of mathematical modeling. This requires the development of digital (Digital Twin) models that reliably describe the technological processes. It seems efficient to create a Digital Twin for individual units, with their subsequent integration into a complex digital model. This approach was applied in the development of models of electrical systems for the new line. Such models should take into account a wide range of real-life physical relationships. At the same time, a three-high continuous train of stands with an idle inter-stand is the least studied technological unit of the new mill. The absence of an electric drive of the middle stand determines the particulars of deformation processes and the stands’ interconnections through the processed metal. To date, a comprehensive study of such objects has not been carried out. Therefore, the task of studying this technological unit is of immediate interest. The presented publication is devoted to the development of digital models of deformation zones of drive stands and idle stands, as well as of their relationship through the processed metal. The task is solved using the example of an operating pilot production line that implements rolling technology with an idle stand. The authors describe individual Digital Twins and present the structure of the complex model of the studied unit. The most important purpose of the model is to use it in the development of a control method for electric drives of stands to ensure the stability of the rolling process. The developed method should provide a reduction in energy consumption due to the use of friction force reserves present in the idle stand. The authors also substantiate the control principle based on continuous monitoring and alignment of critical angles in the deformation zones of the drive stands. The paper describes a structure of the control system and explains the technical implementation of this principle. The results of mathematical modeling and oscillograms of typical transient processes are presented. The advantages provided by implementing the proposed control method are shown. The work provides an indirect confirmation of the adequacy of the model to the physical object. Recommendations are given on the use of the developed Digital Twin in the study of rolling processes on sheet and sectional mills.